"Well, I Think There Is Great Variation…": A Qualitative Study of Oncologists' Experiences and Views Regarding Medical Criteria and Other Factors Relevant to Treatment Decisions in Advanced Cancer. (3rd January 2013) - Schildmann, Jan; Tan, Jacinta; Salloch, Sabine; Vollmann, Jochen
Abstract : CME Learning Objectives: List non‐medical factors that influence decisions about limiting treatment in advanced cancer. Discuss the problems associated with value‐based treatment recommendations. Describe possible strategies for improved ethics and evidence‐based treatment decision making in advanced cancer. Background: Surveys indicate considerable variation regarding the provision of cancer treatment at the end of life. The variation cannot be fully explained by differences concerning the clinical situation or patients' preferences. The aim of this qualitative study was to explore medical oncologists' experiences with advanced cancer, as well as their views of the relevance of medical and nonmedical criteria for decisions about limiting treatment. Methods: Qualitative in‐depth interviews were conducted with physicians working in medical oncology in tertiary care hospitals or district general hospitals in England. Purposive sampling and qualitative analysis were performed. Results: Physicians reported that a number of nonmedical factors influence professional decisions about the offering or limiting of cancer treatment in advanced cancer in addition to medical criteria. Physicians' individual judgments about the benefit of treatment, as well as the amount of their clinical experience, were cited as such factors. In addition, the physicians' perceptions of the patient's age and life circumstances were reported to influence their treatment decisions. Multiprofessional team discussions and the systematic collection of relevant clinical data regarding the outcomes of different treatment approaches in advanced cancer were suggested as strategies to improve the quality of treatment decisions. Conclusion: The findings of this study provide explanations for the variation in treatment in advanced cancer. Making value judgments explicit and gathering more appropriate clinical data on the outcomes of treatment near the end of life are prerequisites for improved ethical and evidence‐based treatment decisions in advanced cancer. Abstract : Considerable variation exists regarding the provision of cancer treatment at the end of life. This qualitative study explores medical oncologists' experiences with advanced cancer and their criteria for decisions about limiting treatment of advanced cancer. Abstract : 摘要 背景 . 调查显示癌症终末期给予的治疗千差万别。这种变异不能完全由临床表现或患者意愿的差异来解释。本次定性研究旨在探索临床肿瘤科医生治疗晚期癌症的经验及其在作出限制治疗的临床决策方面的医学和非医学标准的相关性。 方法 . 在英格兰三级保健医院或地区综合医院肿瘤内科医生中开展定性的深入访谈，进行立意抽样和定性分析。 结果 . 据医生报告，除医学标准之外，提供或限制晚期癌症治疗的专业决策还受到大量非医学因素的影响。非医学因素包括医生对治疗获益的个人判断及其临床经验的累积程度。此外报告还显示，医生对患者年龄及其生活环境的认知也影响其治疗决策。对于晚期癌症的不同治疗手段获得的结果，提倡多专科团队讨论系统性收集的相关临床数据，这一策略有助于提高治疗决策的质量。 结论 . 本研究结果为晚期癌症的治疗变异提供了解释。对临终治疗结果作出有价值的清晰判断并收集更合适的临床数据，是改善晚期癌症伦理与循证治疗决策的先决条件。